Examining the impact of media use during the COVID-19 pandemic on environmental engagement - Gibson, Kristin E.; Sanders, Catherine E.; Lamm, Alexa J.; Lamm, Kevan W. (Frontiers in Environmental Science, 2022)
The COVID-19 pandemic led to global public health campaigns enacting strict orders to slow the spread of the disease. The public health initiatives were communicated broadly through diverse news sources and social media channels, spreading both factual information and misinformation about the environmental benefits related to the shelter-in-place orders. This quantitative study of United States residents (N = 1,048), guided by selective exposure theory, examined if demographics, news and/or social media source use, and public knowledge of environmental changes that took place as a result of COVID-19 shelter-in-place orders predicted intent to engage in environmentally-conscious behavior. Results indicated demographics and social media used intent to engage in environmentally-conscious behaviors. Future public engagement in environmental behaviors is critical for environmental sustainability and the media may provide one avenue for engaging the public in environmental behaviors. Discussion points include environmental communication strategies and understanding messaging strategies within the politicization process of communicating about environmental issues during the COVID-19 pandemic.